Epidemiology of eating disorders in Latin America: a systematic review and meta-analysis. Issue 6 (November 2016) - Kolar, David R.; Rodriguez, Dania L. Mejía; Chams, Moises Mebarak; Hoek, Hans W.
Abstract : Purpose of review: Eating disorders are currently not considered to be limited to Western culture. We systematically reviewed the existing literature on the prevalence of eating disorders in Latin America. Recent findings: Of 1583 records screened, 17 studies from Argentina, Brazil, Chile, Colombia, Mexico, and Venezuela were included in the analysis. Most studies reported point-prevalence rates and only three studies provided lifetime and 12-month prevalence rates. We found a mean point-prevalence rate of 0.1% for anorexia nervosa, 1.16% for bulimia nervosa, and 3.53% for binge-eating disorder (BED) in the general population. Heterogeneity for bulimia nervosa and BED was large. This meta-analysis indicates that the prevalence of anorexia nervosa seems to be lower, whereas the prevalence of bulimia nervosa and especially of BED seems to be higher in Latin America than in Western countries. Summary: Our findings show that eating disorders are common mental disorders in Latin America. However, some facets of Latin American culture might be protective for the development of anorexia nervosa and increase the risk for bulimia nervosa and BED. Further studies investigating the epidemiology of eating disorders and their relation to culture in Latin America are needed. Video abstract: http://links.lww.com/YCO/A35 Spanish abstract: http://links.lww.com/YCO/A36 Abstract : Supplemental Digital Content is available in the text